KEPENTINGAN AMERIKA SERIKAT BELUM MERATIFIKASI ARMS TRADE TREATY (ATT) - Perdana, Budi Cipta; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is trying to explain about the interest of United States of America that have yet ratified the Arms Trade Treaty even although have signed it in 2013. United States is the country with the world's biggest transfer value since 2007, the value of this great transfer used by the US as a tool to run the national interest and foreign policy toward countries that are considered to have a strategic position.Arms Trade Treaty emerged in 2013 after being adopted by the UN General Assembly. ATT aims as a treaty regulating the arms trade internationally, especially conventional weapons exist in the world. Arms Trade Treaty regulate the small arms to warship, ATT should be able to protect the rights of citizens who are oppressed due to the use of illegal conventional weapons.The United States considers ATT violate the second amendment of the US constitution, and prevent the achievement of points of US foreign policy related to conventional weapons stated in the conventional arms transfer policy. The United States viewed Arms Trade Treaty as a barrier in achieving US national interests, so the US will be difficult to provide assistance to its allies, maintain superiority and hegemony in the world of international politicsKeyword: ratified, transfer value, national interest, foreign policy, violate, superiority